Residential self-selection in travel behavior: Towards an integration into mobility biographies - Joachim Scheiner (Journal of Transport and Land Use)
The debate on residential self-selection (RSS) in the travel field seeks to answer the question of whether and to what extent spatial differences in traveling may be explained in spatial terms or to what extent, rather, they are explained by the unequal spatial distribution of people’s social and personal characteristics, particularly their neighborhood and travel preferences. Arguing primarily from a European—specifically, German— perspective, this paper makes a case for integrating the RSS-travel link into the mobility biographies approach that has emerged over the past decade. This approach addresses travel behavior as being embedded in other “spheres” of an individual’s life course, most notably the household and family biographies, the employment biography, and the residential biography. This paper argues that stability and change in travel behavior must be considered not only in concert with residential location choice, but also in the wider context of life course, in which residential choices themselves are embedded. Some unresolved issues in the RSS-travel debate that seem to be of key importance for the current debate are discussed, including various aspects of residential location choice, the role of preferences, and implications for spatial planning and transport planning. The benefits of taking a biographical perspective are also pointed out.